2021
DOI: 10.21823/2311-2905-2021-27-1-37-52
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of 3D Implants with Bioactive Properties for Treatment of Extensive Bone Defects: Experimental Study

Abstract: Background. The problem of replacing extensive bone defects remains relevant. The use of implant structures with bioactive properties can stimulate osteogenesis, which will improve the final treatment result.The aim of the study. In an in vivo experiment, to study the possibility of replacing an extensive defect in the bone diaphysis with a personal bioactive cellular 3D implant and evaluate the long-term results of its use.Materials and Methods. In an in vivo experiment, adult large mongrel dogs (n = 8) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Products from PCL with the inclusion of hydroxyapatite (from 10 to 50 wt %) were studied in the treatment of fractures of long bones in animals, treatment of bone defects and experimental limb lengthening. Experimental studies revealed a high biological activity of this new type of intraosseous implants: pH of the environment remained at the level of 6-7, bone union of tibial fractures occurred within 1 month, external fixation index for limb lengthening did not exceed 20 days/cm in monofocal procedures [98]. CONCLUSION Thus, ceramic polymer composites are commercially available nowadays for treatment purposes.…”
Section: обзор литературыmentioning
confidence: 84%
See 3 more Smart Citations
“…Products from PCL with the inclusion of hydroxyapatite (from 10 to 50 wt %) were studied in the treatment of fractures of long bones in animals, treatment of bone defects and experimental limb lengthening. Experimental studies revealed a high biological activity of this new type of intraosseous implants: pH of the environment remained at the level of 6-7, bone union of tibial fractures occurred within 1 month, external fixation index for limb lengthening did not exceed 20 days/cm in monofocal procedures [98]. CONCLUSION Thus, ceramic polymer composites are commercially available nowadays for treatment purposes.…”
Section: обзор литературыmentioning
confidence: 84%
“…However, the main shortcoming of ceramics is its fragility. Therefore, bioinert metals and alloys with a calcium phosphate coating can be used for fabrication of orthopedic devices for the musculoskeletal system, which experiences significant mechanical loads [37][38][39][40]. The coating provides biological compatibility and expressed biological activity in the formation of bone tissue around the metal.…”
Section: обзор литературыmentioning
confidence: 99%
See 2 more Smart Citations